Comparison of injury risk indicators in amateur female rugby players from different countries - Ondřej Sikora; Michal Lehnert (Journal of Kinesiology and Exercise Sciences)
Background: Most specific rugby movements require an efficient stretch-shortening cycle (SSC). Reactive strength index (RSI) and leg stiffness have been considered a reliable measure of SSC capability and an indicator of ACL injury risk. The aim of this study was to assess and compare absolute leg stiffness (ALS) and RSI in amateur female rugby players from different countries.Methods: Players of three female rugby teams participated in the study: the female Czech team, the junior female Czech team, and the female university English team. Twenty repetitions of the submaximal bilateral hopping test were used for the calculation of ALS. RSI was obtained from 5 repetitions of the maximum hop test. Results: The values of the basic statistics were as follows: the female Czech team (median, mean SD): ALS, 25.3 kNm–1, 25.4 3.6 kNm–1; RSI, 0.53, 0.60 0.24; the junior female Czech team (median, mean SD): ALS, 22.7 kNm–1, 23.1 4.6 kNm–1; RSI, 0.37, 0.42 0.19, and the female university English team (median, mean SD): ALS, 22.7 kNm–1, 24.0 3.5 kNm–1; RSI, 0.61, 0.59 0.20. Only a between-group comparison of RSI of the female Czech team and the junior female Czech team (p = 0.04, r = 0.37, medium effect) showed significant differences. Conclusion: No significant differences between groups were found, except for Czech teams of different ages in RSI. The lower values of ALS and RSI compared to other studies can potentially be associated with a higher risk of ACL injury.